2014
DOI: 10.17122/ogbus-2014-4-153-173
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Method for Predicting Field Dosage of Kinetic Hydrate Inhibitor

Abstract: The increased application of low dosage hydrate inhibitors in oil and gas production has made it necessary to develop a method for determining the consumption rates of kinetic hydrate inhibitors, as no techniques are currently available for that purpose. The method was developed in the experiments with the kinetic hydrate inhibitor SONHYD-1801A, representing a stereoregular copolymer of N-vinylpyrrolidone and caprolactam. The currently used technology for application of kinetic hydrate inhibitor SONHYD-1801A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Thus was Faresov taught to communicate in his Saratov prison, and Chudnovskii aided in giving order to the tormenting noise of the House of Preliminary Detention. 45 The circulation of these keys is evidenced in the archives of the Peter and Paul Fortress-on several occasions in this period, guard searches turned up written codes (fig. 6).…”
Section: Knocking Language: Revolutionary Initiationmentioning
confidence: 98%
“…Thus was Faresov taught to communicate in his Saratov prison, and Chudnovskii aided in giving order to the tormenting noise of the House of Preliminary Detention. 45 The circulation of these keys is evidenced in the archives of the Peter and Paul Fortress-on several occasions in this period, guard searches turned up written codes (fig. 6).…”
Section: Knocking Language: Revolutionary Initiationmentioning
confidence: 98%
“…There he married Elena Medvedeva, who bore his child, but soon died of tuberculosis. 41 During his years of exile, he continued to write-two popular novels, more autobiographical stories, and a sharp criticism of Russian and Ukrainian antisemitism. George Kennan of Siberia and the Exile System fame, met Machtet during his survey of political prisoners in 1885-86 and considered him "one of rising novelists of Russia.…”
Section: About the Authormentioning
confidence: 99%
“…It was shown that electrolyte solutions can be considered not only as a thermodynamic, but also as a kinetic inhibitor of hydrate formation. In [14], a comparative analysis of hydrate formation inhibitors of various types of action was carried out: thermodynamic, anti-agglomerate, kinetic, and the advantages and disadvantages of each class of reagents were considered. It was found that the dosage of kinetic inhibitors of hydrate formation is tens of times lower than the classical thermodynamic inhibitor of methanol, which significantly reduces operating costs when protecting pipelines from gas hydrates.…”
Section: Introductionmentioning
confidence: 99%